How a brand's controversial behaviour can impact its image - Mitha, Zainab (The IIE, 2017)
Although there are many definitions of what a brand is, brands in their primary form are social constructs (Klopper & North, 2011). Which means that no matter what a brand puts out intending to be their brand identity, a brand is what their consumers decide they are. With this comes subjective views of a brand from the public. Unfortunately, some brands display controversial behaviour, often resulting in a negative brand image. The aim of this study as mentioned in the title was to uncover how the controversial behaviour of a brand can affect their brand image, as well as to educate brands on the power of consumer perception. The objectives of this study were to determine how controversial behaviour can affect a brand's image, investigate how a brand’s identity can sway public opinion and to determine how much power the public has over a brand’s image. With the use of qualitative research, the aim of this study is to aid businesses in understanding the importance of paying attention to consumers, and being mindful of their brand image. By examining the success or mistakes of other brands, the study should guide business owners in successfully conducting their own brand identities. The small scale qualitative study involved in-depth interviews with 12 members of the target audience. Themes in primary research prove that respondents appear to feel guilty about supporting brands that exhibited controversial behaviour, but still support the brand as they want the specific product provided. The key findings and insights found from both primary and secondary research aided the study in making sound recommendations for brand owners.
Keywords: Brands; Brand Image; Brand Identity; Branding